Punching Shear Resistance of Reactive Powder Concrete Flat Slabs (Al-Mansour Journal, 2022)
This work is devoted to studying the mechanical properties of reactive powder concrete(RPC) and modified reactive powder concrete (MRPC) as a material as well as studying the punching shear behavior of RPC and MRPC slabs. The experimental program includes investigating the effect of steel fiber volumetric ratio (Vf) and absence of coarse aggregates on some important mechanical properties of RPC and MRPC such as compressive strength, uniaxial stress-strain relationship in compression, splitting tensile strength and modulus of rupture. Additional experimental tests are also conducted to study the effect of Vf, steel reinforcement ratio (ρ) and slab thickness on the punching shear behavior (in terms of loaddeflection response, load-strain response and ultimate failure load) of simply supported reinforced RPC slabs having dimensions of 1000×1000× 50 or 70 mm under concentrated load at the center of the slab.
Keywords: MRPC; steel reinforcement ratio (ρ); steel fiber volumetric ratio (Vf)